Relationship between Cognitive Impairment and Behavioural Disturbances in Alzheimer’s Disease Patients - Serra, Laura (Behav Neurol, 2010)
Background and Aims: Alzheimer’s disease (AD) is a neurodegenerative disorder in which the patients can exhibit some behavioural disturbances in addition to cognitive impairment. The aims of the present study were to investigate the relationship between severity and rate of decline of the cognitive and behavioural impairment in patient with AD. Methods: 54 AD patients were assessed at baseline and after 12 months with the Mental Deterioration Battery (MDB), the Alzheimer’s Disease Assessment ScaleCognitive (ADASCog) and the Neuropsychiatric Inventory (NPI10). Results: MDB was more accurate than ADASCog in the early diagnosis of AD. Conversely, ADASCog was more sensitive at revealing the progression of cognitive decline. Depression, Apathy and Anxiety are the most frequent and severe behavioural disturbances at baseline. At followup Delusions and Irritability increased significantly. Significant correlations were observed between severity of cognitive impairment and behavioural disorders both at baseline and in the progression rate passing from T0 to T12. Conclusions: Severity and progression rate of behavioural and cognitive alterations in patients with AD are significantly associated.